Molecular genetic characteristics of the carbapenem resistant Klebsiella pneumoniae KP254 strain as a representative of the highly virulent strain evolutionary branch - A. E. Alekseeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
Here we provide molecular and genetic characteristics of the Klebsiella pneumoniae KP254 clinical strain belonging to clonal group 23 based on the genome-wide sequencing data. It is known that representatives of such clonal group exert highly virulent properties and cause community-acquired infections. Phenotypically, K. pneumoniae KP254 strain is characterized by multidrug resistance, including carbapenems. The determinants of antibiotic resistance (blaSHV-1, oqxAB, fosA) and pathogenicity encoding fimbriae 1, 3 types and the siderophore yersineobactin synthesis were found in the chromosome structure. However, there was uncovered the lack of conjugative element ICEKp1, the pathogenicity island KPHPI208, and the allantoin regulon genes which are often found in highly virulent strains. Analyzing nucleotide sequences in silico allowed to reveal the replicons of incompatibility group plasmids for FII, FIAHI1/FIIK, Col440I, ColpVC, FIBK, FIIpCRY. Combining contigs relative to reference sequences by using the BLASTN service allowed to identify two putative antibiotic resistance plasmids IncFII and IncFIIpCRY as well as one virulence plasmid IncFIBK. The determinants of the aerobactin siderophore, the RmpA2 mucoid phenotype regulator as well as heavy metal resistance genes constitute the virulence plasmid structure. The virulence plasmid nucleotide sequence coverage comprised 93% relative to the virulence plasmid pK2044 with 99.38% identity level; the genomic regions responsible for the salmochelin and RmpA protein synthesis were deleted. The set of antibiotic resistance determinants identified in the mobilome structure includes the genes for beta-lactamase LAP-2 (IncFIIpCRY plasmid) — a TEM-1 analogue, as well as extended-spectrum beta-lactamase CTX-M-55 (IncFII plasmid), both of which are rarely recorded in the Russian Federation. Additionally, widespread genes blaOXA-1, aac(3’)-IIa, ΔcatB4, aac (6’)-Ib-cr, tet(A), qnrSI, sul2, catA2 were also found in the plasmid DNA. The carbapenemase genes are absent in the resistome structure, whereas the examined strain exerts carbapenem resistance. The analysis of the ompK35 and ompK36 porin gene translated sequences revealed mutational changes which resulted in emerged stop codon within the ompK35 gene, whereas OmpK36 amino acid sequence contains a large number of substitutions, insertions, and deletions. The changes identified serve as one of the factors determining the carbapenem resistance. A synergistic effect may be accounted for by activity of the efflux pumps found in the structure of the K. pneumoniae KP254 genome, particularly AcrAB-TolC and KpnEF. Thus, the strain examined by us preserves the most significant signs specific to the highly virulent evolutionary branch Klebsiella strains, and at the same time, acquires the multidrug resistance genetic determinants.